Ab-initio Quantum Mechanical Study of Akdalaite (5Al2O3· H2O): Structure and Vibrational Spectrum - Demichelis, Raffaella; Noel, Y.; Zicovich-Wilson, C.; Roetti, C.; Valenzano, L.; Dovesi, R. (IOP, 2008)
The structure and the vibrational spectrum of akdalaite (5Al2O3·H2O, also known as tohdite) have been investigated at the periodic ab-initio quantum-mechanical level by using a high quality Gaussian type basis set and the hybrid B3LYP Hamiltonian with the CRYSTAL06 code. Three space groups proposed in the literature, namely P63mc and its two P31c and Cmc21 subgroups, have been considered, obtaining essentially the same energy (the largest total energy difference is 0.2 kJ/mol per cell) and geometry.The harmonic frequencies at the ?? point have been computed. Isotopic substitution and graphical representation permit a complete classification of normal modes in terms of simple models (octahedra and tetrahedra modes, hydrogen stretching and bending). The Al-O octahedra and tetrahedra modes appear below 880 cm-1, Al-OH bending modes are located in the range 870-900 cm-1, and OH stretching modes are at 3330-3400 cm